Palladium mediated domino reaction: synthesis of isochromenes under aqueous medium. Issue 1 (2nd January 2020) - Punia, Lavisha; Ramesh, Karu; Satyanarayana, Gedu
Abstract : Isochromenes have been synthesized using palladium-catalyzed C–C and C–O bond forming reactions starting from ortho -bromo tertiary benzylic alcohols and internal acetylenes. Abstract : Isochromenes have been synthesized using palladium-catalyzed C–C and C–O bond forming reactions starting from ortho -bromo tertiary benzylic alcohols and internal acetylenes. Notably, this domino process is feasible by using the green solvent, water. The protocol exhibited a broad substrate scope and afforded various isochromenes.